2010
DOI: 10.1007/s12206-010-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating flow patterns in a channel with complex obstacles using the lattice Boltzmann method

Abstract: In this work, mesoscopic modeling via a computational lattice Boltzmann method (LBM) is used to investigate the flow pattern phenomena and the physical properties of the flow field around one and two square obstacles inside a two-dimensional channel with a fixed blockage ratio, 1 4 β = , centered inside a 2D channel, for a range of Reynolds numbers (Re) from 1 to 300. The simulation results show that flow patterns can initially exhibit laminar flow at low Re and then make a transition to periodic, unsteady, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In the streaming stage, particle at position x after time dt move to x+dx in the direction of its velocity. The collision stage involves only those, real valued particle distribution function arriving at each node although in some other cases (such as multicomponent and multiphase flows) particle distribution function at other nodes may also influence the collision step [6].…”
Section: Methodsmentioning
confidence: 99%
“…In the streaming stage, particle at position x after time dt move to x+dx in the direction of its velocity. The collision stage involves only those, real valued particle distribution function arriving at each node although in some other cases (such as multicomponent and multiphase flows) particle distribution function at other nodes may also influence the collision step [6].…”
Section: Methodsmentioning
confidence: 99%
“…An unstable flow pattern which consists of a periodic vortex shedding pattern behind the obstacle is called a von Karman vortex street. In order to make a detailed comparison of the velocity profiles of the flow pattern phenomena, we found that the Re crit for the flow pass a triangle obstacle is less than the Re crit for flow pass a square obstacle in [12] whereas the same parameters investigations. It was noticed that the flow pattern pass the triangle obstacle generates periodic vortex shedding patterns more quickly than the flow pattern pass square obstacle as shown in Figure 4.…”
Section: Jiraporn Reunsumritmentioning
confidence: 96%
“…It can be seen that there are large fluctuations in velocity for most of the length of the channel but that the fluctuations become small in far wake near the channel outlet. Moreover, we found that the velocity behind the triangle obstacle is more fluctuations than the velocity behind the square obstacle (see Figures 5(a) The instantaneous velocity at the centerline of channel for Re 100 = (a) a triangle obstacle and (b) a square obstacle [12].…”
Section: Jiraporn Reunsumritmentioning
confidence: 98%
See 2 more Smart Citations